Taking action in the first five years to increase career equality: the impact of professional relationships on young women’s advancement - Olsen, Katie; LaGree, Danielle (My University, 2023)
Purpose The purpose of this paper is to examine how young women understand and make meaning of their status as early-career women (ECW) in the creative communication industry, which is typically dominated by male leadership. It explores how professional relationships influence their transition into full-time employment and influences their career trajectories. Design/methodology/approach Interviews with 31 women in the first five years of their communication careers provided insights into how they experience professional relationships in the workplace in relation to leadership advancement. Inductive coding, a feminist organizational communication lens and literature on mentorship and role modeling was used to explore the standpoint of these young women. Findings Young women understand that professional relationships are necessary for acclimation and professional development. Our analysis revealed an intersection of three distinct ways these relationships help young women cultivate a strong career foundation, positioning themselves for leadership opportunities. Practical implications This study provides insight into the experiences of ECW, a group significantly overlooked by industry and research as a way to increase career equity. Findings from this study guide programmatic and socialization practices to help young women overcome barriers. Originality/value Developing a deeper understanding of women worker’s realities, this research encourages industries to regard the entire career path, emphasizing the importance of beginning socialization experiences in the workplace. It offers actionable managerial practices, and it drives a new scholarly focus on a demographic critical to closing the leadership gender gap.
Keywords: Early career; Gender; Feminism; Mentorship; Strategic communication; Female leadership